(untitled) (Third Sector Social Economic Review, 2024)
This study investigates the determinants of financial fragility in the Fragile Five and EU Fifth Round Enlargement Countries using data for the period 2002-2020. The study was motivated by the motivation of obtaining evidence to reveal the determinants of financial fragility using the Panel Logit econometric model. As a result of the study, findings on the determinants of financial fragility were obtained. In the study, it was observed that private sector debt, inflation, countries’ fragility index, interest expenditures, housing loans, consumer loans affect financial fragility significantly and in the same direction. Decision makers and policy makers should pay more attention to these indicators in their strategies to reduce financial fragility. Contrary to the international literature, there is no empirical study in the national literature that considers “crises” as a dependent variable in the measurement of financial fragility. In the Turkish literature, several variables have been used in the measurement of financial fragility. This study, which reveals the determinants of financial fragility by focusing on global and national crises, is expected to contribute to the financial literature as it is the first of its kind in the national literature.